(untitled) (Experimental biology, 2016)
Haemodynamic indexes are related to the age-related features of the physiological systems of organism, in particular systems of circulation of blood. The different types of loading cause the sharp increase of consumption of oxygen in nervous and muscular systems of child. Were investigated age-related features of the cardiovascular system in children of school age. We investigated the basic hemodynamic parameters: heart rate, systolic and minute blood volume and blood pressure at rest and after dynamic load. According to the results of our study revealed age and gender indicators of physiological characteristics of the cardiovascular system.